EGEE site administration made easy - Oliveira, B. (2010)
His paper presents the results of the continuous development of the EGEE roll, after its seminal presentation. While the first version was focused on the installation and initial configuration of an EGEE site, this work aims to provide administrators with an intuitive and user friendly tool to perform the most common administration tasks. The management of the site's configuration, virtual organisations and updates are merged under a single command that can be used from the central Point-of-Presence (POP). Taking advantage of the capabilities offered by the base linux distribution, administrators are now armed with a tool that centralises the management tasks, and can shorten the time required to perform these same tasks. This paper describes how the tool was created and how to use it to simplify administration tasks.